1999
DOI: 10.1366/0003702991945263
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectrum of β-Carotene Using Laser Lines from Green (514.5 nm) to Near-Infrared (1064 nm): Implications for the Characterization of Conjugated Polyenes

Abstract: We have studied the Raman spectrum of β-carotene using excitation wavelengths from visible (514.5 nm) to near-infrared (1064 nm). Qualitatively, the spectrum appears independent of the choice of excitation wavelength, although this is not true in detail; in particular, the ratio of the intensities of the νC-C and νC=C fundamentals to their overtones and combinations varies with the excitation wavelength. The inelastic neutron scattering spectrum shows no evidence for unusual dynamics in this system, and the UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 26 publications
2
43
1
Order By: Relevance
“…The optical image Figure 5. The Raman spectrum of carotenoid (Parker et al, 1999), chlorophyll (Chen et al, 2004), and triglyceride (cf. Fig.…”
Section: Chemical Composition Mappingmentioning
confidence: 99%
“…The optical image Figure 5. The Raman spectrum of carotenoid (Parker et al, 1999), chlorophyll (Chen et al, 2004), and triglyceride (cf. Fig.…”
Section: Chemical Composition Mappingmentioning
confidence: 99%
“…The analysis of the image of the spectrographed cell allowed us to calculate the volume of algal lipid bodies in absolute units, to be used as a reference measurement. The overall sensitivity of the Raman analysis could be increased by several orders of magnitude using the resonance effect taking place when the excitation wavelength matches the absorption maximum, around 490 nm for β-carotene (Parker et al 1999). We have observed severalfold increase in sensitivity using pre-resonant excitation of β-carotene at 532 nm.…”
Section: Discussionmentioning
confidence: 81%
“…All these, except lutein, have 11 conjugated C=C bonds [66], and it has been demonstrated that their Raman spectra are close to that of the well documented β-carotene [67]. Carotenoids produce three characteristic peaks in the Raman spectrum [68][69][70][71][72][73]. Thus, β-carotene-a representative carotenoidexhibits two intense peaks at 1150 cm -1 and 1521 cm -1 arising from inplane stretching vibrations of C-C and C=C bonds respectively, and a third peak occurs at 1008 cm -1 , created by an in-plane rocking movement of methyl groups (CH 3 ) connected to the polyene chain backbone [74].…”
Section: Raman Spectroscopic Analysismentioning
confidence: 83%